O Grupo Maré de Artes e a comunhão ritualística: um jogo entre sujeitos de f(r)icção - Souza, Tatiane Cunha de (2017)
This research has as its central study the creative process and the Ritual Scenic Experiences built by the participants linked to the Grupo Maré de Artes – Programa Mais Cultura Nas Escolas, of the Escola Municipal Edinor Avelino – Macau/RN, where the researcher worked as a Theatre Teacher, between the years 2014 and 2016. This creative process was instigated from educational paths that were experienced and that focus on the principles and ritualistic procedures of the scene and the game. From the experience with Bando La Trupe, developing public art experiences; through the Arkhétypos Grupo de Teatro and the proposition of the art of encounter; getting to Unaluna and the concepts/practices of the Mithodology in Art and Artetnography, the researcher points out art of f(r)iction, the student-active as a subject of f(r)iction, which rubs his real and fictional stories, strolling between the real and the imaginary, in a constant f(r)iction from him with himself, with each other and with the community where he is inserted (LYRA, 2015).